(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study was created to examine the fuzzy logic principles used in the thermal energy assessment of a box-style solar cooker under the specific meteorological conditions in Chennai, Tamilnadu, India. With containers made of copper, aluminum, bottom side, and bar plate coated in black paint & (Al2O3) for the system, various cooking tests of food items have been produced. The following fuzzy logic rules are specifications. It is accepted to provide the manufacturer with a brief window of opportunity for improving the cooker.